2018
DOI: 10.1038/s41598-018-26611-1
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate action in curbing the incidence of liver injury triggered by Diethylnitrosamine by declining oxidative stress via Nrf2 and NFκB regulation

Abstract: Unearthing and employment of healthy substitutes is now in demand to tackle a number of diseases due to the excessive repercussions of synthetic drugs. In this frame of reference pomegranate juice (PGJ) is a boon comprising of anthocyanins and hydrolysable tannins, known for its anti-oxidant and anti-inflammatory properties. Despite various documented roles of PGJ, there are no studies on antifibrotic potential in NDEA-induced mammalian liver fibrotic model. Hepatic fibrosis in rats was induced by the intra-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 109 publications
(101 reference statements)
5
14
0
Order By: Relevance
“…The protective role of NRF2 in liver fibrosis by ameliorating liver injury and inhibiting HSC activation has been reported previously . It is possible that the beneficial effects of SPD and NRF2 activation on ameliorating CCl 4 ‐induced liver fibrosis could be independent of the effects on HSCs.…”
Section: Discussionsupporting
confidence: 53%
“…The protective role of NRF2 in liver fibrosis by ameliorating liver injury and inhibiting HSC activation has been reported previously . It is possible that the beneficial effects of SPD and NRF2 activation on ameliorating CCl 4 ‐induced liver fibrosis could be independent of the effects on HSCs.…”
Section: Discussionsupporting
confidence: 53%
“…These observations are most likely attributed to the presence of hydrolysable polyphenols, specifically ellagitannins, which were considered to be the most active antioxidants among the tannins contained therein. These compounds (elagic acid, punicalagin, punicalin and galagid acid) have been shown to have increased antioxidant and pleiotropic effects and are believed to act in synergy [59,60]. Our findings were found to be similar to studies of Husain et al [61] , Bachoual et al [62] and seem to be compatible with Esmaillzadeh et al [63] as they demonstrated that pomegranate juice significantly reduce the total cholesterol level.…”
Section: Discussionsupporting
confidence: 91%
“…5 ) provided clear evidence of organ toxicity, similar to those associated with known hepatotoxins and nephrotoxins. 52 , 54 , 55 , 56 It also provided the much needed correlation with observed changes in biochemical indices ( Table 3 ). However, differences in liver and kidney histology do not seem to follow a specific pattern for both single and 28 days of repeated doses.…”
Section: Discussionmentioning
confidence: 97%